UNDERSTANDING THE IMPACTS OF FINANCIAL TECHNOLOGY IN THE SOCIETY 5.0 ERA - Mbate, Clarasiska Anasthasia; Windjiarto, Windjiarto; Halawa, Forman; Sinaga, Hizkia Edwar (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Financial Technology (FinTech) aims to achieve a competitive market advantage based on technology (digitalization). This study focuses on figuring out the effects of financial technology in the era of Society 5.0, in which humans can create new values from existing technological transformations to reduce social and economic inequalities in society in the future. This research used a systematic literature review method of 68 articles screened from the Scopus database. Fifty-five impacts of FinTech in the Society 5.0 which can help organizations understand the importance of using fintech are found in this study. The research only focuses on one database. Whereas the aims only focus on the impact of fintech, thus subsequent researchers can continue and develop the same topic using other databases (for example, ScienceDirect) and try to figure out other topics related to fintech (for example, causal factors consequence).Keywords: Financial Technology, Finance, Society 5.0